Mammalian Target of Rapamycin (mTOR) and the Proteasome Attenuates IL-1β Expression in Primary Mouse Cardiac Fibroblasts - Torp, May-Kristin; Yang, Kuan; Ranheim, Trine; Husø Lauritzen, Knut; Alfsnes, Katrine; Vinge, Leif E.; Aukrust, Pål; Stensløkken, Kåre-Olav; Yndestad, Arne; Sandanger, Øystein (Frontiers in Immunology, 2019)
BAbstract Background: IL-1β is a highly potent pro-inflammatory cytokine and its secretion is tightly regulated. Inactive pro-IL-1β is transcribed in response to innate immune receptors activating NFκB. If tissue damage occurs, danger signals released from necrotic cells, such as ATP, can activate NLRP3-inflammasomes (multiprotein complexes consisting of NLRP3, ASC and active caspase-1) which cleaves and activates pro-IL-1β. NLRP3 activation also depends on NEK7 and mitochondrial ROS-production. Thus, IL-1β secretion may be regulated at the level of each involved component. We have previously shown that NLRP3-dependent IL-1β release can be induced in cardiac fibroblasts by pro-inflammatory stimuli. However, anti-inflammatory mechanisms targeting IL-1β release in cardiac cells have not been investigated. mTOR is a key regulator of protein metabolism, including autophagy and proteasome activity. In this study we explored whether autophagy or proteasomal degradation are regulators of NLRP3 inflammasome activation and IL-1β release from cardiac fibroblasts. Methods and results: Serum starvation selectively reduced LPS/ATP-induced IL-1β secretion from cardiac fibroblasts. However, no other inflammasome components, nor mitochondrial mass, were affected. The mTOR inhibitor rapamycin restored pro-IL-1β protein levels as well as LPS/ATP-induced IL-1β release from serum starved cells. However, neither serum starvation nor rapamycin induced autophagy in cardiac fibroblasts. Conversely, chloroquine and bafilomycin A (inhibitors of autophagy) and betulinic acid (a proteasome activator) effectively reduced LPS-induced pro-IL-1β protein levels. Key findings were reinvestigated in human monocyte-derived macrophages. Conclusion: In cardiac fibroblasts, mTOR inhibition selectively favors pro-IL-1β synthesis while proteasomal degradation and not autophagy is the major catabolic anti-inflammatory mechanism for degradation of this cytokine.